Various interfaces mobile meeting (VIMM) / Mohd Halmi Hanapiah - Hanapiah, Mohd Halmi (2002)
VIMM is about software use for conversation (similar as conference) applied on various devices. The software acts as a host that connects with other users. The host handles the software to activate the session. Once the session is activated, the host invites participants to start the session. Then the entire user can interact with each other using their various devices. This paper presents a study on the portion of VIMM objectives that are: to identify the use of IP protocol as medium transmission for enable wired and wireless communication for VIMM, to identify the types of multimedia compression used and the associated protocols needed, to compare similarity and difference of VIMM and other similar products and proposing the VIMM model architecture. The study is based on a literature research from resources such as technical reports, research papers and books. From this study a review on VIMM particularly on its wired and wireless mode and architecture are made.